The operator ebook A novel. - Berg, Gretchen (2024)
"What if you could listen in on any phone conversation in town? With great humor and insight, The Operator by Gretchen Berg delivers a vivid look inside the heads and hearts of a group of housewives and pokes at the absurdities of 1950s America, a simpler time that was far from simple. Think The Marvelous Mrs. Maisel  in the suburbs with delicious turns of jealousy, infidelity, bigotry, and embezzlement thrown in for good measure. The Operator is irresistible!"  —Kathryn Stockett, author of the New York Times bestselling novel The Help A clever, surprising, and ultimately moving debut novel, set in a small Midwestern town in the early 1950s, about a nosy switchboard operator who overhears gossip involving her own family, and the unraveling that discovery sets into motion. In a small town, everyone knows everyone else’s business . . . Nobody knows the people of Wooster, Ohio, better than switchboard operator Vivian Dalton, and she’d be the first to tell you that. She calls it intuition. Her teenage daughter, Charlotte, calls it eavesdropping. Vivian and the other women who work at Bell on East Liberty Street connect lines and lives. They aren’t supposed to listen in on conversations, but they do, and they all have opinions on what they hear—especially Vivian. She knows that Mrs. Butler’s ungrateful daughter, Maxine, still hasn’t thanked her mother for the quilt she made, and that Ginny Frazier turned down yet another invitation to go to the A&W with Clyde Walsh. Then, one cold December night, Vivian listens in on a call between that snob Betty Miller and someone whose voice she can’t quite place and hears something shocking. Betty Miller’s mystery friend has news that, if true, will shatter Vivian’s tidy life in Wooster, humiliating her and making her the laughingstock of the town. Vivian may be mortified, but she isn’t going to take this lying down. She’s going to get to the bottom of that rumor—get into it, get under it, poke around in the corners. Find every last bit. Vivian wants the truth, no matter how painful it may be. But as Vivian is about to be reminded, in a small town like Wooster, one secret usually leads to another. . . .